Extension of the Thar desert -A myth or reality ? : Part I- Analysis of rainfall - CHOWDHURY, A; ROHAM , SG; QAIKWAD, SD (MAUSAM, 1987)
In view of recent contradictory statements about the extension of the Thar desert this problem has been examined from meteorological point of view. For this purpose meteorological elements for stations located within-30 and 50cm annual isohyets have been subjected to vigorous statistical tests. Eighty years data (1901-1980) have been used in the analysis. In this part, besides rainfall, the march of the desert has also been studied from climatic water balance. The study reveals that the rainfall in the buffer zone between 30 and 50 cm Isohyets in not experiencing any systematic decreasing trend. Study of climatic water balance also: does not support the. View of any climatic shifts, taking place, around the Thar desert. Thus, from the rainfall and the water balance considerations, It can be safely said that the so called onward march of the Thar desert is not a reality.